Governance and public management : strategic foundations for volatile times - Greitens, Thomas J. ;Jesuit, David K.;Roberge, Ian (London, United Kingdom : Routledge, Taylor & Francis Group, 2014)
The key difference between success and failure for most governance systems is adaptation, specifically the ability to resolve the existing social, cultural, economic and environmental challenges that constrain adaptation. Local, regional and national systems differ in how they are designed to organize effective participation and create innovative ideas for missions, goals, strategies and actions. They also differ in how they build the effective coalitions needed to adopt, guide and protect strategies and actions during implementation, and how to build competence and knowledge to sustain implementation. This book presents the strategic foundations for government$1 (Bs role in fostering and adapting to societal transformation in a volatile world. It shifts the focus of the discipline from an overtly retrospective analysis to a prospective analysis, incorporating the role of foresight techniques and instruments. Above all, it stimulates debate about the practical implications of governance as an emergent future-oriented framework of public management. This challenging book aims to facilitate dialogue and discussion between academics and practitioners, and encourage advanced students to take a new perspective on Public Management during these volatile times.s
Public management for volatile times : towards deliberative, collaborative, and adaptive policy governance / Frank Baber -- Developing prospective in public management -- Foresight : transforming government / Ian Roberge -- Strategic management in turbulent environments : re-inventing regional economic hubs in Canada / Charles Conteh -- Constructing public management futures during fiscal stress / Lawrence Sych -- Collaboration and conflict -- Public management of sustainable energy development : how national policies help or hinder future energy security / Thomas Rohrer & Rick S. Kurtz -- Managing services and voicing public values : the water sector in Italy / Filippo Giordano, Riccardo Mussari & Filippo Caputo -- Collaboration : conflict contradiction in American public management : a "paradoxical thinking" foresight / Morris Bidjerano -- Deliberation and trust -- Citizen deliberation in prospective public management : recognizing its value, overcoming its challenges / Thomas J. Greitens & J. Cherie Strachan -- Inequality, government performance, and trust in public managers / David K. Jesuit -- Trust and twenty-first century public management / M. Ernita Joaquin.
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION